Distributional concerns and public opinion: EV subsidies in the U.S. and Japan. (May 2022) - Lim, Sijeong; Dolsak, Nives; Prakash, Aseem; Tanaka, Seiki
Abstract: This paper explores whether perceptions about distributive inequity shape public support for energy transition policies. The introduction of electric vehicles (EVs) is an important policy priority for the decarbonization of road transportation. Because high sticker prices restrict EV sales, governments offer consumers EV subsidies. However, some are concerned that subsidies may favor certain groups and industries. Using a conjoint experiment, we examine the public preference for EV subsidies in the U.S. and Japan., . In the U.S., there is a concern that EV subsidies help the high-income (i.e., individual-focused concerns), while the prevailing concern in Japan is whether they favor foreign companies which are the first movers in the EV industry (i.e., industry-focused concerns). We embed a vignette experiment within the conjoint experiment to prime the respondents with individual- and industry-focused distributional concerns. In both countries, regardless of the priming they received, our respondents favor universalistic subsidies that are inclusive of the high-income and luxury/foreign cars to subsidies that are more progressively targeted (i.e., exclusive of the rich and luxury cars) or favoring domestic firms. As such, recent EV policy discourse centering on distributional politics does not appear to reflect public opinion. Highlights: Politicians want EV subsidies for low-income buyers and domestic car manufacturers. Conjoint experiment finds that public favors EV subsidies for all buyers and cars. Vignette experiment finds that distributional discourses do not affect public. Partisanship does not influence public support for universal EV subsidies. Policy-makers should be aware of the elite-mass gap over EV subsidy preferences.